IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBENTUKAN DISIPLIN BELAJAR SISWA - Nasution, Majidah; Asiah, Nur; Simanungkalit, Nurlelawati; Ulfah, Sania; Aisyah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is a systematic process designed to develop the full potential of students, including cognitive, affective, and psychomotor aspects. In order to achieve academic success, one important character value is the discipline to study. Akan tetapi, realitas di lapangan menunjukkan bahwa tingkat kedisiplinan siswa masih belum optimal. Hal ini tampak dari kebiasaan datang terlambat, menunda penyelesaian tugas, dan ketidakpatuhan terhadap peraturan yang berlaku di sekolah. This study aims to describe how character education is implemented to foster learning discipline among students at SD IT Al-Munawwar. The research method used was a qualitative approach with a case study design. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, dan dianalisis dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. The results of the study show that character education is implemented through activities, teacher modeling, consistent enforcement of the rules, and integration of character values in the learning process. These implementations have a positive impact on improving students' learning discipline, as evidenced by their punctuality, compliance with rules, and responsibility in completing tasks. Overall, the implementation of character education creates a disciplined and conducive learning environment and supports the improvement of educational quality.